SANTUN BERBAHASA DALAM DAKWAH - Indrawati Indrawati (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
The use of language in preaching becomes essential to achieve the purpose of dakwah. Intermediate language will be used in conveying messages of propaganda. Da'wah is an activity that is carried out in an effort to invite each other to goodness that comes from divine teachings. Therefore, the call must be delivered in ways that polite. One is the polite use of language. A missionary or proselytizing actors are expected to provide spiritual touches through the right choice of words and appropriate. The accuracy and suitability rules embodied in the words clear, precise, and interesting. Behavior mannered and polite language accompanied with exemplary preaching can deliver on the glory of human life.